Research Progress of Oxygen Corrosion of Tubing Materials in Injection Environments in Oil and Gas Fields - SONG Wenwen, XIE Junfeng, ZHAO Mifeng, YUAN Juntao, TAN Fengling, FU Anqing, LI Xuanpeng (Cailiao Baohu)
The problem of pipe corrosion in oil and gas field injection wells is prominent， causing serious resource waste and safety hazards in the oil and gas industry， and oxygen corrosion has become one of the main causes of pipe perforation failure.Herein， this article reviewed the research progress on oxygen corrosion of pipes in oil and gas field injection environments in recent years， with a focus on the effects of injection well conditions and injection parameters (such as process conditions， temperature， oxygen content， flow rate， etc.) on oxygen corrosion of metal materials.Meanwhile，the mechanism and protection methods of oxygen corrosion were explored，and the shortcomings in current research were analyzed.Finally，based on the requirements of oil and gas field engineering，suggestions were put forward for future research in this field.